2021
DOI: 10.3389/fonc.2020.596355
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-Rich Diet, GSTP1 rs1871042 Polymorphism, and Gastric Cancer Risk in a Hospital-Based Case-Control Study

Abstract: BackgroundChronic gastritis along with Helicobacter pylori (H. pylori) infection has been implicated in inflammatory response-related genes linked to the causation of gastric cancer. Glutathione S-transferase Pi (GSTP1) plays a role in regulating oxidative stress and detoxification against carcinogenesis. In this study, we aimed to determine whether an antioxidant-rich diet is associated with gastric cancer risk and identify how this association could be altered by GSTP1 genetic variants.MethodsThis study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…Several dietary factors (i.e., an antioxidant based diet or soy products including isoflavones) have been reported to interact with genetic factors affecting GC risk [ 13 , 14 , 27 ]. Kim et al (2020) reported that the polymorphism of glutathione S-transferase Pi ( GSTP1 ) rs1871042 increases the risk of GC (OR= 1.55, 95% CI = 1.10–2.16) [ 13 ]. However, they found that an antioxidant-rich diet might reduce the risk of GC according to the rs1871042 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several dietary factors (i.e., an antioxidant based diet or soy products including isoflavones) have been reported to interact with genetic factors affecting GC risk [ 13 , 14 , 27 ]. Kim et al (2020) reported that the polymorphism of glutathione S-transferase Pi ( GSTP1 ) rs1871042 increases the risk of GC (OR= 1.55, 95% CI = 1.10–2.16) [ 13 ]. However, they found that an antioxidant-rich diet might reduce the risk of GC according to the rs1871042 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Yang et al (2012) reported that participants with a risk allele in the MAP3K1 gene (rs16886448 and rs252902) showed significantly higher GC risk [ 5 ]. Fortunately, several dietary factors (i.e., an antioxidant based diet or soy products including isoflavones) have been reported to interact with genetic factors that affect GC risk [ 13 , 14 ]. In particular, soy products are abundant in phytoestrogens such as genistein, daidzein, and glycitein [ 15 ], which can mimic the function of estrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Diamonds show the pooled effect. Abbreviations: RR, relative risk; Ca, number of cases; Co, number of controls; n, number of events; N, number of patients [ 4 , 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ].…”
Section: Figurementioning
confidence: 99%
“…and lifestyle (e.g., smoking and alcohol consumption) factors through a multistage process of gastric carcinogenesis [42][43][44]. Our previous study has examined the association between the incidence of GC and the dietary antioxidant capacity based on the oxygen radical absorbance capacity [45]. Several studies have indicated…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%